Analiza zapotrzebowania na wsparcie oraz wsparcia otrzymanego przez kobiety z rakiem piersi = Analysis of demand for support and of support received by women with breast cancer - Szadowska-Szlachetka, Zdzisława Cecylia; Janczaruk, Marzena; Dziurko, Jolanta; Starosławska, Elżbieta; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2015)
Szadowska-Szlachetka Zdzisława, Janczaruk Marzena, Dziurko Jolanta, Starosławska Elżbieta, Stanisławek Andrzej. Analiza zapotrzebowania na wsparcie oraz wsparcia otrzymanego przez kobiety z rakiem piersi = Analysis of demand for support and of support received by women with breast cancer. Journal of Education, Health and Sport. 2015;5(2):246-259. ISSN 2391-8306. DOI: 10.5281/zenodo.16104 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A246-259 https://pbn.nauka.gov.pl/works/546317 http://dx.doi.org/10.5281/zenodo.16104 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. Analiza zapotrzebowania na wsparcie oraz wsparcia otrzymanego przez kobiety z rakiem piersi Analysis of demand for support and of support received by women with breast cancer Zdzisława Szadowska-Szlachetka2, Marzena Janczaruk1, Jolanta Dziurko1, Elżbieta Starosławska1, Andrzej Stanisławek2 1Centrum Onkologii Ziemi Lubelskiej im. św. Jana z Dukli 2Uniwersytet Medyczny w Lublinie, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej Streszczenie Wstęp Rak piersi jest najczęściej występującym nowotworem wśród kobiet w Polsce. Jego leczenie jest długotrwałe wielokierunkowe, czasami wiąże się z okaleczeniem, uciążliwymi skutkami ubocznymi leczenia. Powoduje to wiele obaw u pacjentek, które przeżywają duży stres związany ze swoją sytuacją zdrowotną. Dlatego też potrzebują one holistycznego wsparcia ze strony rodziny i pracowników służby zdrowia. Cel Celem niniejszej pracy była ocena zapotrzebowania na wsparcie społeczne (informacyjne, emocjonalne, instrumentalne, duchowe i materialne) u pacjentek leczonych z powodu raka piersi. Materiał i metoda Badania zostały przeprowadzone wśród pacjentek leczonych w Centrum Onkologii Ziemi Lubelskiej im. Św. Jana z Dukli w Pododdziale Chemioterapii Dziennej, I Oddziale Onkologii Klinicznej, IV Oddziale Radioterapii Onkologicznej, V Oddziale Chirurgii Onkologicznej. Dotyczyły one 112 pacjentek leczonych w tej placówce. W badaniu zastosowano technikę wywiadu z użyciem autorskiego kwestionariusza ankiety. Wyniki Pacjentki leczone z powodu raka piersi potrzebują wsparcia informacyjnego (59%), emocjonalnego (51%) i duchowego (59%)Mniejszy odsetek badanych ma zapotrzebowanie na wsparcie instrumentalne (48%) i materialne (45%). Najczęściej wsparcia emocjonalnego dostarczają pacjentkom członkowie rodzin (71%), zaś pielęgniarki są dawcami wsparcia informacyjnego udzielanego w czasie leczenia uzupełniającego, to jest chemioterapii (25%) i radioterapii (13,39%). Wnioski Pacjentki leczone z powodu raka piersi potrzebują najczęściej wsparcia informacyjnego, emocjonalnego i duchowego, rzadziej instrumentalnego i materialnego. Słowa kluczowe: rak piersi, wsparcie oczekiwane, zapotrzebowanie na wsparcie. Summary Introduction Breast cancer is the most common cancer among women in Poland. Its treatment is long-term and multidirectional, sometimes associated with mutilation, burdensome side effects of treatment. This causes a lot of concern in patients who are experiencing high stress due to their health situation. Therefore, they need a holistic support from family and health care workers. Purpose The purpose of the study was to determine demand for social support (information, emotional, instrumental, spiritual and material) at patients treated for breast cancer. Material and method The study was conducted among patients treated in St Johns’ Oncology Center in Lublin (COZL) in Daily Chemotherapy subdivision, I Department of Medical Oncology, IV Department of Radiation Oncology, V Department of Oncological Surgery. They concerned 112 patients treated in this institution. In the study used was interview technique using author’s survey questionnaire. Results Patients treated for breast cancer need information (59%), emotional (51%) and spiritual (59%) support. Smaller percentage of respondents needs instrumental (48%) and material (45%) support. Emotional support is most commonly provided to patients by family members (71%), whereas nurses provide information during the follow-up treatment, i.e. chemotherapy (25%) and radiotherapy (13.39%). Conclusions Patients treated for breast cancer most frequently need information, emotional and spiritual support, less frequently instrumental and material support. Key words: breast cancer, expected support, demand for support.